Designing A Place Value Chart to Help Pupils In Basic Three Subtract Three-Digit Numbers - Frimpong, Samsford Atta; Dwumfuo, Kofi Agyeman; Soadwa, Enoch; Antwi, Felicia (International Journal of Scientific Research and Management (IJSRM), 2024)
The action research conducted was about designing a place value chart to help pupils in Basic three, subtract three-digit numbers.  The project was undertaken in the Nsuta R/C Primary School in the Sekyere Central District in the Ashanti Region.The targeted population for the study was Nsuta R/C Primary Three pupils.  The population size was 33 pupils, made up of 20 boys and 13 girls.  A sample size of 20 pupils was selected for the study, comprising 9 boys and 11 girls.  Purposive sampling procedure was considered in selecting the pupils in order to give pupil who needed help the opportunity to participate in the action research.Instruments used in the collection of data included observation, and test.  Related literature review on the research was conducted.  Pre- Intervention tests and a post-intervention test were administered. The post-Intervention test results showed tremendous improvement in pupils’ performance.  According to the results of the study, primary schools should be encouraged to use materials like place value charts and sticks, especially in the Early Grade levels, to help pupils learn how to solve subtraction problems involving three-digit numbers.